The Influence Of Corporate Social Responsibility On Firm Value Through Corporate Reputation And Financial Performance - Finda QONITA; Moeljadi MOELJADI; Kusuma RATNAWATI (International Journal of Environmental, Sustainability, and Social Science, 2022)
This research aims to examine and analyze the direct and indirect effects of the variables of Corporate Social Responsibility (CSR), Corporate Reputation, and Financial Performance on Firm Value. This type of research is explanatory research with quantitative methods. The sampling technique used by the researcher is the non-probability sampling method. The research sample comprised 18 companies listed on the Indonesia Stock Exchange from 2017 to 2019. This research uses secondary data. The data analysis method used Path Analysis with SPSS software. The study's results to examine the direct effect show that CSR has a significant positive impact on corporate reputation. CSR, corporate reputation, and financial performance have a significant positive impact on firm value. CSR has no significant effect on financial performance. The results of the indirect effect test show that CSR on firm value through financial performance has no significant impact. The influence of CSR on the firm value through the corporate reputation has a significant effect. Therefore, only the Corporate reputation can mediate the relationship between the influence of CSR on firm value. This study shows investors and company management the importance of implementing and disclosing Corporate Social Responsibility in companies related to the benefits of increasing firm value.